2009
DOI: 10.1016/j.mce.2009.02.016
|View full text |Cite
|
Sign up to set email alerts
|

The pancreatic β-cell as a target of estrogens and xenoestrogens: Implications for blood glucose homeostasis and diabetes

Abstract: . The pancreatic β-cell as a target of estrogens and xenoestrogens: Implications for blood glucose homeostasis and diabetes. Molecular and Cellular Endocrinology, Elsevier, 2009, 304 (1-2) Please cite this article as: Nadal, A., Alonso-Magdalena, P., Soriano, S., Quesada, I., Ropero, A.B., The pancreatic ␤-cell as a target of estrogens and xenoestrogens: Implications for blood glucose homeostasis and diabetes, Molecular and Cellular Endocrinology (2008), doi:10.1016/j.mce.2009 This is a PDF file of an unedite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
187
0
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 263 publications
(202 citation statements)
references
References 89 publications
5
187
0
7
Order By: Relevance
“…One might raise the question whether the maternal endocrine status before placentation and/or after IVF stimulation possibly influences glucose tolerance in women with PCOS. Furthermore, elevated estrogen levels lead to an excessive stimulation of estrogen receptor alpha in the pancreatic beta cells, producing exaggerated insulin signaling that may cause an increased state of insulin resistance in peripheral tissues (Nadal et al, 2009). Moreover, IVF is known to lead to an increased risk for maternal complications, including GDM independently of the presence of PCOS (Pinborg et al, 2004) (Shevell et al, 2005).…”
Section: Other Methods Of Ovulation Inductionmentioning
confidence: 99%
“…One might raise the question whether the maternal endocrine status before placentation and/or after IVF stimulation possibly influences glucose tolerance in women with PCOS. Furthermore, elevated estrogen levels lead to an excessive stimulation of estrogen receptor alpha in the pancreatic beta cells, producing exaggerated insulin signaling that may cause an increased state of insulin resistance in peripheral tissues (Nadal et al, 2009). Moreover, IVF is known to lead to an increased risk for maternal complications, including GDM independently of the presence of PCOS (Pinborg et al, 2004) (Shevell et al, 2005).…”
Section: Other Methods Of Ovulation Inductionmentioning
confidence: 99%
“…Recent studies have shown the importance of oestradiol for energy balance and glucose homeostasis [76]. Therefore, EDCs may also play a key role in this pathophysiology.…”
Section: Diabetes Mellitusmentioning
confidence: 99%
“…Epidemiological data have pointed to a relationship between exposure to dioxins, impaired tissue glucose transport and utilisation, as well as diabetes [78]. BPA may affect the pancreatic cells [76]. It has been demonstrated that long exposure to BPA leads to tissue insulin resistance [79].…”
Section: Diabetes Mellitusmentioning
confidence: 99%
See 2 more Smart Citations